Comparative lifecycle costs and emissions of electrified powertrains for light-duty logistics trucks. (April 2023) - Feng, Yanbiao; Dong, Zuomin
Abstract: Light-duty logistics trucks play an important role in transporting and dispatching goods in urban and suburban regions. Their powertrain electrification can reduce air pollution and carbon dioxide emissions with different levels of investment. This study examines six electrified powertrain solutions with identical yearly mileage for these trucks, considering the lifecycle carbon dioxide emissions and total ownership costs. The battery-electric powertrain was found to lead in both areas, regardless of the additional battery pack replacement costs. The hydrogen fuel cell powertrain, capable of fast refueling, appears as a competing solution if hydrogen fuel price drops. Finally, the internal combustion engine hybrid electric powertrain with no range anxiety showed a limited carbon dioxide emissions reduction and cost saving, presenting fading competitiveness with added carbon–neutral consideration. This quantitative comparison method provides insights into electrified powertrain design and selection for light-duty logistics trucks.